Synthesis, crystal structure and Hirshfeld surface analysis of 5,5-diphenyl-3-(prop-2-yn-1-yl)imidazolidine-2,4-dione - Abderrazzak El Moutaouakil Ala Allah; Chiara Massera; Walid Guerrab; Abdulsalam Alsubari; Joel T. Mague; Youssef Ramli (Acta Crystallographica Section E: Crystallographic Communications)
The new phenytoin analogue 5,5-diphenyl-3-(2-propyn-1-yl)imidazolidine-2,4-dione, C18H14N2O2 (3), was obtained through an alkylation reaction with propargyl bromide via the phase-transfer catalysis method, and its structure was determined via single-crystal X-ray diffraction analysis. The asymmetric unit of 3 consists of two independent molecules differing mainly in the orientation of the propynyl group. Each molecule forms an inversion dimer through pairs of N2—H2...O2 hydrogen bonds. The crystal structure is further consolidated by C—H...O and C—H...π interactions. The contributions of the different interactions towards the crystal packing were further analysed using Hirshfeld surface and fingerprint plots, showing that the largest contribution comes from the H...H contacts (45%).